A measure of students motivation, attitude and parental influence towards interest in STEM career among Malaysian form four science stream student - Razali, Fazilah; Talib, Othman; Abdul Manaf, Umi Kalthom; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2017)
There is an increasing demand for STEM-based careers. The awareness of the importance of STEM-based careers should be instilled in students, as early as secondary school level. The formation of students’ interest should begin by understanding the needs of students and identifying factors that can encourage students’ interest in STEM careers. The purpose of this study is to identify clearly, factors that influence the formation of students’ interest in STEM careers, among science-stream students. The descriptive regression research design uses a questionnaire versions, that have been modified, which are the Science Motivation Questionnaire II (SMQ), the Student Attitude towards STEM (S-STEM) and the Interest in STEM Career and Parental Authority Questionnaire (PAQ). Overall, students are influenced by attitude, motivation and parental influence in the formation of interest in STEM careers. Motivation to learn science and parental influence is clearly seen as influencing students’ interest in STEM careers, with a high reliability of .913 dan .918, respectively. Additional studies on students in other STEM fields such as Agricultural Science, Computer Science, Home Economics, Sports Science, Design and Technical studies, need to be carried out to identify the formation of interest in STEM careers on a broader scale.